2000
DOI: 10.1002/jor.1100180324
|View full text |Cite
|
Sign up to set email alerts
|

Biological and mechanical characteristics of the interface between a new swelling anchor and bone

Abstract: We recently evaluated the peak pullout loads for anchors made from our new copolymeric swelling-type material compared with anchors made of a nonswelling material. In vitro and in vivo peak pullout loads of these anchors were evaluated after different intervals of implantation in the lateral femoral condyles of New Zealand White rabbits. Scanning electron microscopy and energy dispersive x-ray analyses were additionally performed on selected retrieved samples after pullout to examine the characteristics of bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…The results presented here demonstrate clearly the existence of an optimal swelling strain beyond which the fixation strength of the swellable anchor does not increase appreciably with an increase in the swelling strain (see Figs. [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented here demonstrate clearly the existence of an optimal swelling strain beyond which the fixation strength of the swellable anchor does not increase appreciably with an increase in the swelling strain (see Figs. [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…(Note that the holding power of traditional metallic anchors are known to be strongly influenced by the cortical layer thickness. 9 ) Gualtieri et al 8 studied the biological and mechanical characteristics of the interface between the swellable anchor and bone in the lateral femoral condyles of New Zealand white rabbits. It was reported that (1) the swellable smooth cylindrical anchors produced from P(MMA-AA) induced radial bone growth, and (2) an average pullout force of 177 N at 4.7% swelling strain and an average pullout force of 102 N at 6.9% swelling strain.…”
Section: Introductionmentioning
confidence: 99%
“…The swelling of the copolymer was constrained by the surrounding bone, and consequently, an interfacial pressure was developed at the bone–polymer interface. This interfacial pressure, in turn, increased the frictional resistance and improved significantly the fixation strength of the implants 6–11. Thus, crosslinked poly(MMA‐AA‐AMA)‐modified bone cement could compensate the shrinkage of bone cement during polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…From our previous studies of crosslinked poly(methylmethacrylate‐acrylic acid‐allylmethacrylate) (poly(MMA‐AA‐AMA)), it is found that this copolymer exhibits the ability to absorb body fluids and swell in a controlled manner 9–13. Gualtieri et al have reported that crosslinked poly(MMA‐AA‐AMA) copolymer is able to induce bone ingrowths in the interface of bone and this copolymer 14. By introducing crosslinked poly(MMA‐AA‐AMA) copolymer into bone cement, the fixation strength in the interface of bone and cement can be improved by the controllable swelling of the modified bone cement, to compensate the shrinkage of the cement during polymerization 15.…”
Section: Introductionmentioning
confidence: 99%